Forecasting Australia`s Olympic performance: Australia to suffer post host letdown in Athens - Clarke, S. R. (2004)
By using some simple methods, we have estimated the total number and mix of medals to be won by Australia in Athens. Better predictions might be obtained by using extra prediction variables, such as the population and GDP of competing countries. Given the resources, more accurate methods, which allow estimation of probabilities of all possible medal totals, could be used. By modeling each individual sport based on past performances, and using a simulation, chances of each Australian competitor in each event could be obtained. The complete Olympic games could then be simulated thousands of times to come up with estimates for Australia`s medal tallies and finishing position in the medal tables. This is similar to the methods we have used for prediction of the AFL finals, Formula 1 World Championship, major tennis tournaments, and World Cups of soccer and rugby. However that would be a big task. Here we have used more global methods, using just the final medal tallies of Australia and other countries. Our estimates should be thought of as expected values, which will be failed to reach or exceeded with 50% chance. Clearly there is much variation possible about that total, but with the methods used here I have not been able to put limits on these predictions. They do seem to be roughly in line with those made by other bodies. Note again the estimates of 10 gold, 14 silver and 16 bronze are made without yet knowing the total number of medals to be awarded. Should this number exceed 1000, we could add an extra medal to each of the gold, silver and bronze totals. Our estimate of 40 medals overall is close to the record 41 medals achieved by Australia in an away Olympics. So Australia has a good chance of bettering this record. Our estimate of 10 gold medals means they have an even better chance of exceeding the record number of 9 Gold won in an away Olympics. But the loss of the home advantage makes it nearly impossible to better the 58 medals and 16 gold to break the performance in Sydney. To do that, Australia will have to wait for another home games. Alternatively, by the year 2048, the natural increase in the number of medals awarded at each Olympics will result in 80 medals if we can win only 4% of those awarded.